Growth performance of heat-stressed broiler chickens fed extruded canola meal - Aljoubori, A.; Idrus, Zulkifli; Soleimani Farjam, Abdoreza; Liang, Juan Boo; Abdullah, Norhani (Faculty of Veterinary Medicine, Universiti Putra Malaysia, 2013)
A study was conducted to determine the effect of dietary inclusion 0, 10, 20 and 30% of extruded canola meal (ECM) on performance of boiler chickens under heat stress. From day 29-35, birds were exposed to either 36±1°C or 23+1oC. Feeding heat-stressed birds with 30% ECM did not depress growth performance but not those under unheated condition. In conclusion, 30% ECM can be included in the diets of heat-stressed broiler chickens without any adverse effect on performance.